Prevalence of hypothyroidism in reproductive age group in rural population of Haryana and its effects on menstrual disturbances - Yadav, Priyanka; Arora, Geetika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Menstrual disorders are a common problem in reproductive age females. These disorders may cause significant anxiety for patients and their families. Thyroid dysfunction is one of the common cause of menstrual irregularities. Aim of the study was to determine the prevalence of hypothyroidism in reproductive age group women (15-45years), describe its various modes of clinical presentation and to assess the menstrual pattern in women with hypothyroidism. Methods: Prospective observational hospital based study during a period of 6 months (January 2020 to June 2020) on patients presenting in OPD in department of obstetrics and gynaecology, SGT medical college, hospital and research institute, Budhera, Gurgaon. Results: Prevalence of hypothyroidism was found to be 52.6% (190 out of total 338 patients) and it increased with increasing age group. 213 patients out of total came with complains of menstrual irregularities. 49.2% with normal menstrual cycle had hypothyroidism while 60.4% presenting with irregular heavy menstrual bleeding had hypothyroidism, p value being 0.019 which was statistically significant. Conclusions: Menstrual irregularities increase with severity of hypothyroidism. So screening for thyroid dysfunction should be included in management plan of menstrual disturbances.